Propuesta de rediseño de la red de datos del gad de Rioverde, provincia de Esmeraldas, bajo la metodología Ppdioo y el diseño Top-Down. - Carrera Santana, Lizeth Nataly (2018)
This project has as an objective to represent the knowledges obtained along my career, proposing the redesign of the data network of the Rio Verde’s municipality canton of the Esmeraldas’s province that will allow to save information and the informatics resources against possible thefts or catastrophes. The redesign allows replace the room of the data located in the main building by a data center that will be build in the administrative’s building. The data center will have a suitable place for equipment and data storage serves, ventilation, structured cabling, security system, electric supply, these considerations are based in the norm ANSI/EIS/TIA569 within the redesign it is proposed that the equipment of core distribution and access be change by equipment of cisco brand. At a logical level with the redesign it will be improve the availability of resources, the redundancy and it will allow to moderate failures and vulnerabilities of security, which will provide to the municipality data network that give reliability to the information. It is also proposed the incorporation of VOIP service with software free, based in asterisk as a central telephone. All of this is simulated through the program opnet where perform an analysis of the initial scenario of the municipality’s net and the scenario proposed of improve, allowing check that the proposal is sustainable.